Evaluasi Parameter Reticulocyte Hemoglobin Equivalen (Ret-He) sebagai uji Skriing Defisiensi Besi pada ibu Hamil Aterm Dalam persalinan - , Dinne Fitriya; , dr. Tri Ratnaningsih, M.Kes, SpPK-K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia still working hard to achieve the objectives of the Millennium Development Global (MDGs) related to maternal and under five mortality, which causes closely linked to nutritional problems. One of nutritional problem in pregnancy with high prevelance in Indonesia including Yogyakarta is iron deficiency. Pregnancy at term have a high risk of iron deficiency due to the increasing demand at thirdmester and blood loss durante partum leading to potentially risk interruption to the mother's health and infant growth and development at golden period. To prevent this permanent impacts, early detection to iron deficiency in pregnant women at term is necessary, in order to assess the adequacy of maternal iron preparation for lactation. Gold standard to asess iron deficiency is iron staining of bone marrow, but this test is very invasive, indirect tests with hematological and biochemical parameters is preferred. Conventional hematological parameters can only detect advanced stages, biochemical parameters can detect early stages but more expensive, less practical due to the need of special preparation, influenced by several factor and limited availability. XT-2000i hematology analyzer from SYSMEX can estimate the hemoglobin content of reticulocytes (Reticulocyte Hemoglobin Equivalent/Ret-He) which are released in the circulation from the bone marrow for 24-48 hours. This test more accurately represent the actual condition of erythropoiesis and has high potential diagnostic accuracy to detect early stages of iron deficiency. This parameter can be applied with just a minimum cost of reagents, using the same sample, not influenced by inflammatory and consistent with biological variation, but affected by conditions of thalassemia trait and megaloblastic anemia.. This cross sectional study aimed to determine the role of RET-He in the screening of iron deficiency in pregnant women at term who will give birth in Yogyakarta, compared with ferritin at cut off value <15 ng /ml which has negative qualitative CRP as the gold standard. Determination of cut-off value Ret-He with optimal sensitivity and specificity using the Receiver Operating Characteristic curve.The diagnostic performance of Ret-He in various cut-off shown in the form of sensitivity, specificity, positive predictive value, negative predictive value, positive and negative likelihood ratio..